Population estimate of Crocodylus moreletii in four sites of the Pantanos de Centla Biosphere Reserve - Rodas-Trejo, Jenner; Ocampo-González, Paola; Mandujano-Camacho, Hernán Orbelín (Ecosistemas y Recursos Agropecuarios, 2022)
The quantiﬁcation of crocodiles in natural environments represents basic information to establish management and conservation strategies for these species. With the aim to estimate the encounter rate (ER), abundance and population structure of Morelet’s Crocodile (Crocodylus moreletii ) in the Pantanos de Centla Biosphere Reserve (PCBR), between the months of September to De- cember 2018, they were carried out monthly night tours in the localities Tabasquillo, Tembladeras, La Mixteca and Lázaro Cárdenas. In total, 797 records were obtained in 16 night counts. In Tembladeras locality, the lowest ER and population size were recorded with 1.12 crocodiles linear km−1 and 54.09 ± 6.31 individuals, respectively, while the highest values are shown in La Mixteca locality with 3.14 crocodiles linear km−1 and 84.79 ± 6.44 individuals. Signiﬁcant differences were found between the individuals observed by transect (H = 14.3457, gl. = 3, p < 0.01). Individuals of all size classes were observed at all four locations. The highest proportions were presented in classes I and II. This information contributes to the knowledge about population ecology and a ﬁrst approximation of the current state of the swamp crocodile and represents the ﬁrst study for C. moreletii in this locaties of the PCBR.